Enterprise Architecture Smart Online Education menggunakan metode TOGAF-ADM - Budi Priswanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The development of information technology today is very supportive of activities in any field. Especially in the field of education, its influence is very important with the role of information technology. Especially in the conditions of the Covid-19 pandemic or after the Covid-19 pandemic, his role is very supportive. There is some passion that learning is not bound by place and time. This is actually the industrial era 4.0, where in today's life everything is already using information technology. The world of education has used information technology a lot, one of which is Smart online education. Because this online education can be used without being limited by space and time. Wherever students can get information or learn independently with video tutorials provided in the Online Education Platform. Before developing the online education platform, it is necessary to carry out Information Technology Planning where the creation of Enterprise Architecture is a Roadmap of the Platform. Enterprise Architecture in this study uses five stages of the eight stages contained in The Open Group Architecture Framework (TOGAF). This study aims to produce a Blueprint Platform for Smart Online Education that utilizes the TOGAF Framework method. The blueprint discusses the Preliminary Phase, Architecture Vision, Business Architecture, Application Architecture, Information Architecture, Technology Architecture and Opportunities and Solutions.